Highly malignant soft tissue sarcoma of the extremity with a delayed diagnosis - Park, Jong Hoon (BioMed Central, 2010)
PURPOSE: To evaluate the characteristics of highly malignant soft tissue sarcoma of the extremity with a delayed diagnosis. MATERIALS AND METHODS: The clinical and radiological characteristics of 18 cases of highly malignant soft tissue sarcomas of the extremity with a delayed diagnosis were determined. RESULTS: Ten men and eight women of mean age 44.8 years (range, 15-79 years) were included in this study. Seven cases of synovial sarcoma, three cases each of alveolar soft part sarcoma and malignant fibrous histiocytoma, two cases each of highly malignant leiomyosarcoma and myxofibrosarcoma, and one case of clear cell sarcoma were enrolled. Times from tumor detection to diagnosis ranged from 1 to 3 years in most cases; three of the seven synovial sarcoma cases took more than 10 years to diagnose. Of the seven cases of synovial sarcoma, five cases of small, superficial located masses were simply excised without a pre-surgical biopsy. Three cases of alveolar soft part sarcoma showed characteristic T1- and T2-weighted high signal intensities with signal voids in MR images. In addition, one synovial sarcoma patient and one alveolar soft part sarcoma patient showed evidence of calcification on plain radiographs. However, no general characteristic clinical findings were found to be common to the 18 cases. CONCLUSIONS: Contrary to general expectations, some soft tissue tumors that grow slowly are painless, and those that occur in superficial limbs may be highly malignant. Thus, even when a slow growing, painless superficial mass is encountered in a limb, physicians should keep the possibility of highly malignant soft tissue sarcoma in mind.